Analisis Laporan Keuangan Untuk Mengukur Kinerja Keuangan (PT. Unilever Indonesia Tbk. Periode 2019-2021) - Risalatin Risalatin; Shalza Yashinta Mayseliandra; Sindy Vebri Permatasari (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This study’s purpose is to determine how the financial performance of PT. Unilever. The method used is descriptive qualitative, namely to explain and provide an overview of the conditions or situations that are the object of research. With data analysis techniques, namely using financial ratio analysis consisting of liquidity ratios, solvency ratios, activity ratios, and profitability ratios. This research was conducted at PT. Unilever The results showed that PT. Unilever so far in measuring the level of success of a business is only simple, namely referring to the financial statements that have been presented in each annual period and which should be done after analyzing financial statements using financial ratios, it is known that the level of good performance resulting from the solvency ratio which always increases every year. period, while the level of poor performance resulting from the liquidity ratio has decreased after experiencing an increase in several periods. In the activity ratio analysis, it is known that PT. Unilever can manage receivables with a fast receivables turnover ratio, but the profitability ratio analysis shows that its financial condition is not good because it has not been consistent in generating profits.Keywords: Financial Reports, Financial Performance, Financial Ratios.